Gender Discrimination Perception among Maritime Students in Turkey - Volkan FİDAN; Esin GÜNAY; Gamze AKPINAR; Can ATACAN (Journal of Eta Maritime Science, 2020)
Gender discrimination is a controversial issue that is being debated around the world, independently the level of development of countries. This discrimination is tried to be prevented by legal regulations.However, itis a practice problem rather than law in business life. The maritime sector is one of the sectors considered to be more prevalent in stereotypes of gender roles. It is thought that this discrimination is applied more in occupational groups that require physical force. It was aimed to determine the perceptions of associate degree students in maritime programmes about gender discrimination related to maritime profession at public universities across Turkey. The result of the study reveals that the perception of gender discrimination is higher among female students than male. Especially Underwater Technology students’ perception of gender discrimination is higher than Maritime Transport and Management, and Yacht Master students. It proves that women can not find any job in the industrial diving sector due to restrictions of Turkish Labor Law although they have education in Underwater Technology programmes.